Exploring the role of clinical educators written feedback in demystifying clinical reasoning skills within the clinical evaluation examination in Physiotherapy: Perspectives from disciplinary expects and novices - Osman, Ayesha (School of Education, 2024)
An Academic literacies (AL) approach to teaching emphasises the need to make disciplinary literacy practices explicit to disciplinary novices who are in the process of entering a discourse community. Clinical reasoning (CR) skills, i.e., the valued practices and ways of being and doing involved in clinical practice, are conveyed to Physiotherapy students in contexts such as clinical supervision. However, the way in which this happens within the key setting of a clinical examination has not been given enough empirical attention. The numerous studies in the field of Physiotherapy clinical evaluation are mostly quantitative and tend to focus on the reliability of assessment tools. Few investigate the role of written feedback in making the values of the disciplines explicit, or how this feedback is received by third year students who are new to clinical practice. This dissertation aims to explore the extent to which the clinical evaluation examination of third year Physiotherapy students at the University of Cape Town serves as a site for the explicit conveying of CR skills. It does this by exploring the role of written feedback provided by disciplinary experts, namely, clinical educators (CEs) to disciplinary novices and explores the extent to which the literacy event of the clinical evaluation provides space for making these explicit to students who are being assessed. The study addresses this question from three interlinked perspectives: firstly, through a Critical Discourse Analysis (CDA) of CEs' feedback in the evaluation rubric that is used to examine students' clinical performance. This is followed by a thematic analysis of interviews with the CEs to gain insight into the disciplinary values and practices on which they draw when assessing and providing feedback to students. The student perspective is assessed through questionnaires where they are required to reflect on their experience of receiving feedback and being socialised into CR for the purpose of becoming competent physiotherapists. The findings highlight the challenges students face when navigating and decoding written feedback as novices to clinical practice. Upon analysis of students' and CEs' perceptions, there is alignment in their understanding of the purpose of the written feedback. The strong themes of ‘knowing the basics' and ‘the importance of communication' emerged from the CE interviews, which is also mirrored in the student reflections. However, students expressed the need for more detailed feedback, as well as positive feedback to strengthen and support good performance. The findings yielded by the CDA of the feedback foregrounds CEs' practice of questioning, which is used as an educational strategy within clinical education, with the intention of developing students' CR skills. The CDA revealed that this practice extends to the CEs' written feedback as well, where the practice of questioning which shapes one literacy event, namely clinical supervision, is transposed onto another, i.e., the clinical examination, as part of providing written feedback. The data from the student questionnaires reflect how the vocabulary/language used within this questioning presents challenges for an effective engagement with the feedback. This study argues that students' challenge with navigating and decoding CEs' written feedback serves to reinforce the expert / novice divide, highlighting the powerful position from which the CEs respond. It is envisaged that the findings can assist CEs in enhancing their feedback practices through greater consciousness of students' access to the discourse. It may also be used to conscientize students about the thinking behind CEs' ways of providing feedback to improve their performance in clinical practice.